Draft genome sequence of a carbapenem-resistant clinical Acinetobacter baumannii revealing co-existence of four classes of β-lactamases. (December 2021) - Jahan, M. Ishrat; Rahaman, Md. Mizanur; Hossain, M. Anwar; Sultana, Munawar
Highlights: Carbapenem-resistant Acinetobacter baumannii DMC-32a was retrieved from an ICU patient. Draft genome sequence analysis revealed the co-existence of four β-lactamase classes. A class 1 integron gene cassette with resistance genes to rifamycin ( arr-2 ) and phenicols ( cmlA5 ) was also identified. ABSTRACT: Objectives: Nosocomial carbapenem-resistant Acinetobacter baumannii is a challenge in the treatment of intensive care unit (ICU) patients. The presence of antimicrobial resistance genes (ARGs) and mobile genetic elements can further complicate effects to combat antibiotic resistance in this post-antibiotic era. The aim of this study was to analyse the molecular basis of carbapenem resistance in A. baumannii strain DMC-32a. Methods: Strain DMC-32a, isolated from a wound swab of an ICU patient, was screened phenotypically and genotypically for carbapenem resistance. The isolate was subjected whole-genome sequencing (WGS) to investigate the resistance mechanisms. Results: Strain DMC-32a was resistant to all tested antibiotics belonging to seven classes, except for the polymyxins. MICs determined against imipenem and meropenem were 512 mg/L and >512 mg/L, respectively. Gene-specific PCR confirmed the presence of bla NDM-1 and intI1 . WGS confirmed the isolate as sequence type ST1053, the presence of four classes of β-lactamases [A ( bla PER-7, bla TEM-116 ), B ( bla NDM-1 ), C ( bla ADC-26 ) and D ( bla OXA-23, bla OXA-51 )], and four genes encoding aminoglycoside-modifying enzymes [ aph(6)-Id, aph(3′′)-Ib, aph(3′)-VI and ant(3′′)-IIc ] conferring resistance to streptomycin, amikacin, kanamycin and spectinomycin. The analysis also confirmed the presence of a class 1 integron gene cassette harbouring ARGs to rifamycin ( arr-2 ) and phenicols ( cmlA5 ). No plasmid replicon was found from the sequence data. Conclusion: The co-existence of four β-lactamase classes in A. baumannii DMC-32a has not been reported previously from Bangladesh and not in this ST elsewhere. The emergence of such a nosocomial pathogen creates the need for effective therapeutics for critically-ill patients and for controlling hospital-acquired infections.